Platelet‐rich fibrin and collagen membrane in the preservation of the alveolar bone: Feasibility of the elemental inorganic composition and scanning electron microscopy analysis - Dias, Fernando José; Arias, Alain; Borie, Eduardo; Fuentes, Ramón
The success of dental implants is related to the amount, quality, and composition of the alveolar bone. The placement of platelet‐rich fibrin (PRF) clot associated with a resorbable collagen membrane (RCM) in a postextraction alveolus is a technique used for ridge preservation. This case report study analyzed the ultrastructural characteristics of cross‐sectioned alveolar bone that received PRF and RCM using scanning electron microscopy and the inorganic composition using “energy dispersive X‐ray spectrometry,” in order to explore the feasibility of this method to clinical studies. Three alveolar bone samples from two male patients (37 and 58 years old), obtained in the procedure of placing the dental implant, were analyzed. Two bone samples previously received PRF and RCM (M37 and M58), the third sample represented a physiological bone formation without treatment (M37‐control). The bone sample M37 showed irregularly shaped islets of calcified material intermingled with connective tissue. The other samples, from the 58‐year‐old patient with PRF and RCM (M58); and the other untreated bone sample from the same 37‐year‐old patient (M37‐control) showed similar ultrastructural morphology with trabecular conformation without islets agglomerations. The inorganic composition analysis showed higher concentrations of calcium and phosphorus in both samples treated with PRF and RCM in comparison to the untreated bone sample. The Ca/P ratio was higher in the M37 sample compared to the others samples. The results showed morphology and inorganic composition differences among the treatments used, suggesting that this method is feasible to analyze parameters of the alveolar bone tissue.